Accuracy of digital impressions for implant-supported complete-arch prosthesis when using an auxiliary geometry device - Hale Arikan; Mehmet Muhtarogullari; Sema Merve Uzel; Mustafa Baris Guncu; Guliz Aktas; Lindsay Simone Marshall; Ilser Turkyilmaz (Elsevier, 2023)
Background/purpose: Digital impressions using intraoral scanners have recently gained popularity. The aim of the present study was to evaluate the fit of full-arch screw-retained cobalt-chromium frameworks fabricated via two different digital impression methods. Materials and methods: An edentulous resin master model with four dental implants was fabricated. Forty cobalt-chromium superstructures were fabricated and evaluated according to four groups. In Group 1, the superstructures were evaluated using an intraoral scanner to generate digital impressions. Group 2 relied on the help of an auxiliary geometric appliance in generation of digital impressions via intraoral scanner. The traditional method of splinted open-tray conventional impressions was designated for Group 3. Finally, the control group (Group 4) relied on scanning of the master model directly with a laboratory scanner. Vertical marginal discrepancy was evaluated, and data obtained were statistically analyzed. Results: The highest mean vertical marginal gap value (80.86 ± 50.06 μm) was observed for Group 1 and statistically higher than Group 2, 3, and 4 (P < 0.05). The lowest mean vertical marginal gap value (41.98 ± 26.33 μm) was measured from Group 4 and statistically similar to Group 2 and 3 (P > 0.05). Conclusion: It has been suggested that the use of auxiliary geometric appliances yields increased scanning accuracy. Frameworks fabricated using the traditional splinted open-tray technique were more reliable compared to those frameworks from digital impressions.